Don't you cry - Kubica, Mary (Don Mills, Ontario : MIRA Books, 2016)
In downtown Chicago, a young woman named Esther Vaughan disappears from her apartment without a trace. A haunting letter addressed to My Dearest is found among her possessions, leaving her friend and roommate Quinn Collins to wonder where Esther is and whether or not she's the person Quinn thought she knew. Meanwhile, in a small Michigan harbor town an hour outside Chicago, a mysterious woman appears in the quiet coffee shop where eighteen-year -old Alex Gallo works as a dishwasher. He is immediately drawn to her charm and beauty, but what starts as an innocent crush quickly spirals into something far more dark and sinister than he ever expected. As Quinn searches for answers about Esther, and Alex is drawn further under the stranger's spell, master of suspense Mary Kubica takes readers on a taut and twisted thrill ride that builds to a stunning conclusion and shows that no matter how fast and far we run, the past always catches up with us in the end.
Keywords: Missing persons -- Fiction; Suspense fiction; Psychological fiction